THE INFLUENCE OF SELF-EFFICACY ON GENDER ROLE IN CAMPUS ORGANIZATIONS - Tsurayya Syarif Zain; Novera Intan Nadiyah; Amelia Novitasari; Aura Lintang Dwi Amanda; Annisa Permata Sari; Rahni Rismawati (Journal of Psychology and Social Sciences, 2023)
This study aims to investigate the influence of self-efficacy on gender roles among psychology students of UIN Raden Fatah Palembang in campus organizations. This research used a quantitative approach and a causal-comparative research design. Causal-comparative research is used to examine the cause-and-effect relationship between two variables where the independent variable has already occurred and cannot be manipulated by the researcher. The independent variable in this study is self-efficacy, while the dependent variable is gender roles. The population in this study is psychology students of UIN Raden Fatah Palembang, and a sample of 30 active students participating in campus organizations was selected using purposive sampling. Data were collected using a Likert scale questionnaire, and data analysis was performed using simple linear regression analysis to test the influence of self-efficacy on gender roles. The collected data were analyzed using statistical software such as SPSS. The results indicate a strong correlation between self-efficacy and gender roles (R = 0.957), and the coefficient of determination (R Square) is 0.917, indicating a strong influence of self-efficacy on gender roles. The decision-making based on the significance value (0.000 < 0.05) and t-value (17.544 > 2.048) shows that self-efficacy has a significant influence on gender roles. The regression equation is Y = 1.951 + 0.922X, where the constant (a) is 1.951, and the coefficient of self-efficacy (b) is 0.922, indicating that an increase in self-efficacy by 1% leads to an increase in gender roles by 0.922. These findings suggest that peer and mentor support can enhance self-efficacy and participation of female students in campus organizations.